Chinese Expert Consensus on Standardized Outpatient Management of Sarcopenia in the Elderly (2024) - Zhang Qin; Kang Lin; Wang Jianye; Xi Huan; Yu Pulin; Zhang Cuntai; Hidenori Arai; Tuo Xiping; Yang Yunmei; Liu Xiaohong (Aging Medicine, 2025)
ABSTRACT Sarcopenia is an age‐related disorder that influences the daily living ability of older adults and interacts with various chronic diseases. Older adults with sarcopenia typically experience a deterioration in their quality of life and healthy lifespan. The number of Chinese persons with sarcopenia is considerable, and the burden of sarcopenia is substantial; however, the specific sarcopenia clinics available for outpatients are insufficient. The promotion of sarcopenia clinics is beneficial for the early identification, standardized diagnosis, and treatment of older adults with sarcopenia, thereby helping to enhance their physical function and quality of life. This consensus incorporates the professional recommendations of Chinese geriatrics experts, synthesizes existing Chinese experiences in establishing sarcopenia clinics, offers guidance for managing sarcopenia clinics, and advocates for early identification, diagnosis, and intervention of sarcopenia in older adults.